Optimality Theoretic Semantics. - Hendriks, Petra; de Hoop, Helen (Linguistics & Philosophy, 2001)
The aim of this article is to elucidate the processes that characterize natural language interpretation. The basic hypothesis is that natural language interpretation can be characterized as an optimization problem. This innovative view on interpretation is shown to account for the crucial role of contextual information while avoiding certain well-known problems associated with compositionality. This will become particularly clear in the context of incomplete expressions. Our approach takes as a point of departure total freedom of interpretation in combination with the parallel application of soft constraints on possible interpretations. These constraints can be contextual, intonational or syntactic in nature. The integration of pragmatic and syntactic/semantic information in a system of ranked constraints is proposed to correctly derive the optimal interpretations in cases of nominal anaphorization, determiner quantification and elliptical comparatives.